555 VISCERAL OBESITY: PREVALENCE, AND IMPACT ON OPERATIVE AND ONCOLOGIC OUTCOMES IN THE CURATIVE MANAGEMENT OF ESOPHAGEAL CANCER. (17th September 2021) - Elliott, Jessie A; Donlon, Noel E; Doyle, Suzanne L; King, Sinead; Beddy, Peter; Donohoe, Claire L; Ravi, Narayanasamy; Reynolds, John V
Abstract:  : Obesity, in particular visceral obesity, is a risk factor for esophageal cancer, but its prevalence and impact on operative and oncologic outcomes is unclear. The aim of this study was to study adipose distribution in esophageal cancer (EC), and to assess its independent impact. Methods: 11 consecutive patients undergoing treatment with curative intent for esophageal cancer were studied. Total (TFA), subcutaneous (SFA) and visceral fat areas (VFA), and fat mass (FM), were determined pre-treatment, preoperatively, and 1 year postoperatively. Visceral obesity was defined by CT at L3 as VFA greater than 163.8 cm2 for men and 80.1 cm 2 for women. All complications were recorded prospectively, including comprehensive complications index, Clavien-Dindo, and pulmonary complications (PPC). Multivariable logistic and Cox proportional hazards regression were utilized to determine independent predictors of operative and oncologic outcome. Results: Visceral obesity (VO) was evident in 290 patients (47.5%), and was associated with BMI-defined obesity, diabetes, metabolic syndrome, Barrett's esophagus (P = 0.001), well-differentiated tumors (P = 0.027), and lower cN stage (P = 0.012). VO did not impact tumor regression grade (TRG) after neoadjuvant therapy. Postoperatively, VO independently predicted anastomotic leak (P = 0.033, OR2.42 [1.07-5.45]) and pneumonia (P = 0.046, OR1.53 [1.01–2.32]), but not in-hospital mortality (P = 0.466), which was 1% overall. VO was associated with significantly improved overall and disease-specific survival on univariable (P = 0.005, Figure), and multivariable analysis (P = 0.026, 0.74 [0.57–0.97]). In survivorship, VO significantly declined, and was evident in just 15.3% at one year postoperatively. Conclusion: VO is linked with Barrett's associated EC, and less aggressive tumour biology. Although it negatively impacted operative outcomes, VO was associated with improved oncologic outcomes, independent of BMI or fat mass, indicating a distinct biologic phenotype, and highlighting the importance of research elucidating the interaction between the visceral fat microenvironment, metabolic dysfunction, and the tumor microenvironment.